البنية الأسلوبية في قصيدة "هذي الملايين" للشاعر يوسف الخطيب - أبو جحجوح، خضر محمد; صالحة، عبدالكريم محمود Salehah, Abdulkarim Mahmoud (المركز الجامعي الونشريسي تيسمسيلت - مخبر الدراسات النقدية والأدبية المعاصرة, 2019)
تهدف هذه الدراسة إلى الكشف عن جماليات البناء الأسلوبي في قصيدة "هذي الملايين" للشاعر يوسف الخطيب من خلال مستويات التحليل الأسلوبي، وهي: المستوى الصوتي، والمستوى الدلالي، والمستوى التركيبي، وما ينبثق عنها من تفريعات أسلوبية. إن في الأسلوبية كشفاً عن ملامح التميز في تركيب الدوال والمدلولات، وصولا إلى الإلحاح على ذهن المتلقي ليستكنه الدلالات الكامنة ضمن منظومة نسقية تسهم في تشكيل لبنات النص وتضامها في مكون شعري له ملامح فارقة تشد المتلقي من جهة، وتصدمه من جهة أخرى بما فيها من انزياحات وتعالقات نصية.
This study aims at accentuating the aesthetic aspect embodied in the stylistic construction of the poem labelled as "These Millions", constructed by the poet Yosuf Al-khatib. The method adopted in doing so is by utilizing the varied levels of stylistic analysis and this includes acoustic, semantic and structural levels, in addition to what might appear as a stylistic variation observed to occur between such levels. In stylistic manifestations there are of excellence in the composition of signifier and significance, to the insistence on the mind of the recipient for the inherent connotations within the poetic of coordination contribute to the formation of the blocks of text and their integration into a poetic component has a distinguishing features that attract the recipient, including the shifts and textual interactions.
Keywords: الادب العربي -- الخطيب، يوسف، ت. 2011 م. -- الشعر العربي